hi i really need help

(-1/3)(1/6)square((-1/3)(1/6)-(-1/3)square))=

1/108(-1/18-1/9)=1/108(-1/9)=1/972

i know i got the wrong answer but i tried to find out several ways but i get the wrong answer " the answer suposed to be 1/648" how \HELP

Results 1 to 3 of 3

- Mar 6th 2006, 05:43 PM #1samarox16Guest

- Mar 6th 2006, 07:16 PM #2

- Joined
- Nov 2005
- From
- New York City
- Posts
- 10,616
- Thanks
- 10

- Mar 6th 2006, 11:48 PM #3

- Joined
- Apr 2005
- Posts
- 1,631

Originally Posted by**samarox16**

If you like to learn/use LaTex, the "a^2" will appear as the familiar "a, squared" as you would write it on paper.

(-1/3)[(1/6)^2]*[(-1/3)(1/6) -(-1/3)^2]

= (-1/3)(1/36)*[(-1/18) -(1/9)]

= (-1/108)*[(-1 +2(-1))/18]

= (-1/108)*[(-3)/18]

= (-1/108)(-1/6)

= 1/648 ------------------answer.